Interaction between Li2Mg(NH)2 and CO: Effect on the hydrogen storage behavior of the Li4(NH2)3BH4 doped Mg(NH2)2-2LiH composite - Gamba, Nadia Soledad; Amica, Guillermina; Arneodo Larochette, Pierre Paul; Gennari, Fabiana Cristina (Pergamon-Elsevier Science Ltd, 2017)
Fil: Gamba, Nadia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina